Cidade-mercadoria e gentrificação: análise do caso da comunidade Parque Araçagi II, localizada na região metropolitana da Grande São Luís/MA - VIANA, Mariana Rodrigues (2019)
This present work investigates the obstacles that the context of the restructuring of cities for capitalist reproduction, in this more recent phase of flexible accumulation of capital, with the financialization of land and housing, presents for the realization of the right to the city, recognized in the national legal field by the urban policy chapter of the Federal Constitution of 1988 and by the City Statute (Law n° 10.257, of 2001), which regulates the appointed chapter. To this end, it discusses how the financialization of land and housing led to the construction of the city-merchandise - this city that seeks to be inserted competitively in the global market, adopting urban entrepreneurship - and as a result of this scenario cities have become more segregated, with the intensification of processes of expulsion of the low-income population in favor of market / patrimonial interests - which is approached as a phenomenon of gentrification - and with the consequent multiplication of urban land conflicts. It also brings reflections on the role that the Judiciary has been assuming in the face of urban land conflicts arising from this conjuncture and what role it could / should assume, based on the urban-legal paradigm inaugurated by the Federal Constitution of 1988 and by the City Statute (Law n° 10.257, of 2001). For this purpose, the study of the case of the Parque Araçagi II community, located in the região metropolitana da Grande São Luís/MA, was adopted as a paradigmatic case of the subject. Therefore, it is a qualitative research, which takes into consideration a case study, adopting among the research techniques, the bibliographic, the documentary and the empirical. The conclusion presented is that the Judiciary has been assuming, in the face of urban land conflicts set in the city-merchandise, a hegemonic performance, which results in the production of socio-spatial segregation, which is pointed out as the result of a civilist patrimonialist paradigm built since the end of the nineteenth century, with the Land Law (Law n° 601, of 1850), which gave absolute contours to property. It is argued that a democratization of justice and a construction of a new legal common sense are necessary for the paradigmatic turn towards the new juridical-urbanistic order that enables counter-hegemonic action, meeting the yearnings of contemporary social complexity of financialized and gentrified cities.